Parallel implementation of local thresholding in Mitrion-C - Kryjak, Tomasz; Gorgoń, Marek (Zielona Góra: Uniwersytet Zielonogórski)
Mitrion-C based implementations of three image processing algorithms: a look-up table operation, simple local thresholding and Sauvola?s local thresholding are described. Implementation results, performance of the design and FPGA logic utilization are discussed.
Keywords: image processing; FPGA; Mitrion-C; local thresholding; reconfigurable systems